Edukasi Perilaku Hidup Bersih Dan Sehat Untuk Siswa Sekolah Dasar Di SDN Mayangan 1 - Yusri Dwi Lestari (Pusat Riset dan Inovasi Nasional, 2023)
Clean and Healthy Living Behavior (CHLB) is a set of behaviors to strengthen the habits of a person, group or community to care about and prioritize health to create a healthier and quality life. In schools, this activity is practiced by students, teachers, and the community in the school environment, so that they can independently improve health, prevent disease, and play an active role in creating a healthy environment. This activity was carried out in the framework of socializing and increasing knowledge about Clean and Healthy Living Behavior (CHLB) in schools, especially for students so they can practice clean and healthy living behaviors, and play an active role in creating healthy schools. This community service activity is carried out by directly educating students at SDN Mayangan 1. The implementation of this activity is in line with the aim of increasing elementary school students' knowledge about clean and healthy living behaviors as well as increasing students' experience and abilities. in counseling. Clean and healthy living behaviors at school that students can do include washing hands with soap, consuming healthy food, exercising, and disposing of trash in its place. By providing education and instilling knowledge about clean and healthy living behaviors from an early age, it will make it easier for students to implement and remember them, and then become a daily habit at school.